SMS Compression System using Arithmetic Coding Algorithm - Rosalina Rosalina; Wahyu Hidayat (IT for Society, 2018)
Short Message Service (SMS) has limitation in the length of its text message, which only provides 160 characters per SMS. It means that if we send more than 160 characters, it will be considered as sending more than one SMS, so that we have to spend more cost for sending SMS. On the other side, the Arithmetic Coding algorithm provides an effective mechanism for text compression. It has performed the great compression result and in many case it was considered as the better compression algorithm than other ones, such as Huffman and LZW (Lempel-Ziv-Welch). This research will implement the Arithmetic Coding algorithm to develop an application that will compress the SMS text message. The concept of Arithmetic Coding will be implemented to compress the SMS text message before it is sent from the sender to the receiver. The application is called CheaperZipper (CZ). This application will handle the sending and receiving SMS in the hand phone by preceding the compression and decompression process.